Methodology for muscle recovery, through motor imagery techniques applying virtual reality - Ovalle Paulino, Denis Christian (2022)
Recovery of movement is a long and hard process for patients. One of the most common problems that occurs is the so-called "phantom limb", which induces the body to feel strange due to the failure to use the injured limb. This process is due to the lack of use of the leg that in most cases is fractured and the long recovery time, so the use of crutches makes the body in conjunction with the brain understand that normal movement of the body is with the leg suspended and always with the help of crutches. In the present work a technique for the retraining of the brain is presented by means of which the brain is taught through the presentation of images if it corresponds to the right and left side of the arms and legs. This retraining makes it possible for the brain to understand the coordinated movement between the arms and legs. In addition to the use of virtual reality, through the OCULUS GEST II lenses, allowing maximum concentration, the results allow to improve the recovery time of patients, the technique can be used both in rehabilitation centers and in the patient's own home patient.